2018
DOI: 10.5194/wes-2018-61
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wind inflow observation from load harmonics: wind tunnel validation of the rotationally symmetric formulation

Abstract: Abstract. The present paper further develops and experimentally validates the previously published idea of estimating the wind inflow at a turbine rotor disk from the machine response. A linear model is formulated that relates one per revolution (1P) harmonics of the in- and out-of-plane blade root bending moments to four wind parameters, representing vertical and horizontal shears and misalignment angles. Improving on this concept, the present work exploits the rotationally symmetric behaviour of the rotor in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The model coefficients F are not all independent, because of the rotational symmetry of the rotor (Bertelè et al, 2019). In a nutshell, the effects on loads caused by the horizontal shear are the same as the ones caused by the vertical shear after a rotation of π/2; the same holds true for the wind misalignment angles.…”
Section: Wind Observer Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The model coefficients F are not all independent, because of the rotational symmetry of the rotor (Bertelè et al, 2019). In a nutshell, the effects on loads caused by the horizontal shear are the same as the ones caused by the vertical shear after a rotation of π/2; the same holds true for the wind misalignment angles.…”
Section: Wind Observer Formulationmentioning
confidence: 99%
“…This is in fact an intrinsic limit of field testing, where an exact ground truth is in general difficult if not impossible to obtain. Realistic simulations and wind tunnel studies as the ones reported in Bertelè et al (2017Bertelè et al ( , 2018Bertelè et al ( , 2019 -where the ground truth is known-may help in this sense.…”
Section: Wind Speed Bin [M/s]mentioning
confidence: 99%
See 2 more Smart Citations
“…A wind state observer for vertical and horizontal shear, yaw misalignment and flow inclination based on flap-and edgewise blade bending moment measurements was formulated and tested through simulations in Bertelè et al (2017) and validated on a scaled experimental turbine in Bertelè et al (2018). In Bottasso et al (2018) a similar observer using flapwise blade bending moments was developed to estimate the average wind speed over four azimuthal sector of the rotor plane.…”
Section: Introductionmentioning
confidence: 99%